Documentary Letters of Credit, Legal Nature and Sources of Law - ALAVI, Hamed (Journal of Legal Studies, 2016)
There is no doubt about risky nature of international trade. Such risk can be conceptualized as country risk, transportation risk, customer risk and etc. Documentary Letters of Credit (LC) are used as a method of payment in international business for many centuries in order to reduce risk of trade specially when parties are located in different countries and do not have precise information from financial standing of each other. In such occasion LC will reduce the risk of trade by shifting payment obligation from buyer as an individual to a payment guarantee of a bank as a legal entity in return for presentation of complying documents with terms of credit by seller. Familiarity with legal nature and different legal frameworks which govern the international operation of documentary letters of credit can facilitate the process of international trade for businessmen and boost national economies. However, lack of knowledge about them can impose huge losses on international traders. Situation will be more complicated when we understand that there are many internationally recognized legal frameworks which can affect the operation of LC and they get frequently updated in order to address technological and economic developments in global market. In this paper, author tries to answer questions regarding (i) what are international legal frameworks governing operation of documentary letters of credit? (ii) which areas of LC operation has been covered by them and (iii) how do they address the legal questions regarding international operation of documentary letters of credit?